2005
DOI: 10.1007/s10350-004-0822-6
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Historic Cohort of Quality of Life and Sexuality in Patients With Rectal Cancer

Abstract: Assessing quality of life with general and specific instruments is helpful to determine whether patients improved through the treatment. The study showed that gender, age, and type of surgery influence sexuality and that quality of life after surgery for rectal cancer is impacted. Because quality of life is a predictor for complications and survival, availability of such data may help to direct supportive treatment to improve outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
66
1
9

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(85 citation statements)
references
References 40 publications
9
66
1
9
Order By: Relevance
“…11 In contrast to men, women who have radical cystectomy or surgery to remove rectal cancer have similar sexual function to healthy controls. 6,12 If pelvic surgery impairs vaginal expansion and lubrication, it seems that women can compensate by using estrogen replacement or water-based lubricants.…”
Section: Sexual Function Gender and Damage From Cancer Treatmentmentioning
confidence: 99%
“…11 In contrast to men, women who have radical cystectomy or surgery to remove rectal cancer have similar sexual function to healthy controls. 6,12 If pelvic surgery impairs vaginal expansion and lubrication, it seems that women can compensate by using estrogen replacement or water-based lubricants.…”
Section: Sexual Function Gender and Damage From Cancer Treatmentmentioning
confidence: 99%
“…Health-related quality of life (HRQOL) outcomes may vary based on sex, as differences for rectal cancer survivors have previously been noted. 3 An intestinal stoma, or ostomy, is the surgical exteriorization of the bowel to the anterior abdominal wall. This may include the small (ileostomy) or large (colostomy) bowel.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported 54.5 in a study by Zając et al [18] among patients with stoma due to rectal cancer. Studies showed that the score of QOL is getting better over time [19] . It has been shown that the QOL among disease-free survivors of rectal cancer after two years HRQOL: health-related quality of life; PF: physical functioning; RF: role functioning; CF: cognitive functioning; EF: emotional functioning; SF: social functioning; CT: chemotherapy; RT: radiotherapy; CRT: chemo-radiotherapy was higher than that in the general population [20] .…”
Section: Discussionmentioning
confidence: 99%